2021
DOI: 10.21873/invivo.12530
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus as a Prognostic Factor for Locally Advanced Rectal Cancer

Abstract: Background/Aim: Currently, the impact of diabetes mellitus (DM) on rectal cancer patients is complex and just partly elucidated. The purpose of this study was to investigate the impact of diabetes mellitus on rectal cancer patients focusing on tumor differentiation grade, neoadjuvant chemoradiotherapy (NACRT) response, disease-free (DFS) and overall (OS) survival. Patients and Methods: Our study's population consisted of a group of 53 patients diagnosed with locally advanced rectal cancer, who underwent NACRT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…However, the findings could be explained by higher age and lower rates of adjuvant therapy, and not due to DM itself, as observed in our multivariate analysis. The findings on univariate analysis is in line with findings by Georgescu et al, 33 however, they could not perform multivariate analysis due to small sample size. The current literature on the effect of DM on the prognosis of rectal cancer remains debatable.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the findings could be explained by higher age and lower rates of adjuvant therapy, and not due to DM itself, as observed in our multivariate analysis. The findings on univariate analysis is in line with findings by Georgescu et al, 33 however, they could not perform multivariate analysis due to small sample size. The current literature on the effect of DM on the prognosis of rectal cancer remains debatable.…”
Section: Discussionsupporting
confidence: 90%
“…The current literature on the effect of DM on the prognosis of rectal cancer remains debatable. 14,15,31,33 The conflicting results of the effect of metformin in population-based studies can be explained at least in part, due to the heterogeneity in study designs (observational/ trials with variable regimens/systematic reviews and meta-analyses) and comparison groups (diabetic metformin users/diabetic non-metformin users/non-diabetics). Further, observational studies studying drug effects tend to be susceptible to time-related biases such as immortal-time bias (misclassification or ignorance of variation in the timing of treatment initiation from cohort entry), time-window bias (cases and controls not matched on the duration of exposure opportunity time within a fixed observation period), and time-lagging bias (when a first-line therapy is compared to the second-or third-line of therapy given at a different disease stage) resulting in potential overestimation of a drug effect when there is none.…”
Section: Discussionmentioning
confidence: 99%
“…L. Fernández-Arce et al revealed that diabetes was a predictor of all-cause mortality in Spanish women with breast cancer [6]. Dragos Eugen Georgescu et al found that rectal cancer patients with diabetes had a higher risk of death than those without diabetes [7]. Kaori Hisanaga et al showed that diabetes was an independent risk factor for OS in patients with lung cancer [8].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research in medical oncology focused on different types of cancer, depending on their frequency, identifying a series of diverse factors [ 7 ] which influenced the evolution of the disease as well as the treatment outcome. While these results led to new therapeutic approaches [ 8 ] which generated better treatment outcomes even in metastatic stages [ 9 , 10 ], cancer is still one of the leading causes of death in the EU and USA [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%